Territorio y vida de las comunidades afroatrateñas Chocó - Colombia (2013)
RESUMEN: Acerca de los autores: García Sánchez, Andrés (Investigador/a) De Almeida Wagner, Alfredo (Coordinador/a) Acevedo Marín, Rosa (Coordinador/a) Palacios, Yuli (Investigador/a) Montoya Arango, Vladimir (Investigador/a)